Tapanuli Central Regency Parent Communication Model in Coastal Traditional Marriage in Sorkam District - Sakinah Azzuhra; Nursapiah Harahap (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
This study uses Aristotelian communication theory, which has three elements of communication aspects, namely speaker, message, and listener, to determine the communication model of the host in traditional coastal marriages in the Sorkam sub-district, Central Tapanuli Regency. This study's methodology employs qualitative data collection methods such as observation, interviews, and documentation. The findings revealed that the mother's communication model in marriage was a.) giving advice or direction to the bride and groom regarding manners, religion, and customs. b.) bathing the bride and groom by placing the two brides on a winnowing and bargaining temping. c.) bridal makeup, which includes everything from traditional attire to make-up. d.) assisting one another in avoiding mistakes or deficiencies in the mating process Meanwhile, the Sibolga community views the host as playing an important role in educating the younger generation about the customs of the coastal community of Sibolga.